Patients with colorectal tumors with microsatellite instability and large deletions in HSP110 T17 have improved response to 5-fluorouracil-based chemotherapy - Collura, A.; Lagrange, A.; Svrcek, M.; Marisa, L.; Buhard, O.; Guilloux, A.; Wanherdrick, K.; Dorard, C.; Taieb, A.; Saget, A.; Loh, M.; Soong, R.; et al. (2014)
Background & Aims: Patients with colorectal tumors with microsatellite instability (MSI) have better prognoses than patients with tumors without MSI, but have a poor response to 5-fluorouracil–based chemotherapy. A dominant-negative form of heat shock protein (HSP)110 (HSP110DE9) expressed by cancer cells with MSI, via exon skipping caused by somatic deletions in the T17 intron repeat, sensitizes the cells to 5-fluorouracil and oxaliplatin. We investigated whether HSP110 T17 could be used to identify patients with colorectal cancer who would benefit from adjuvant chemotherapy with 5-fluorouracil and oxaliplatin. Methods: We characterized the interaction between HSP110 and HSP110DE9 using surface plasmon resonance. By using polymerase chain reaction and fragment analysis, we examined how the size of somatic allelic deletions in HSP110 T17 affected the HSP110 protein expressed by tumor cells. We screened 329 consecutive patients with stage II–III colorectal tumors with MSI who underwent surgical resection at tertiary medical centers for HSP110 T17.Results: HSP110 and HSP110DE9 interacted in a 1:1 ratio. Tumor cells with large deletions in T17 had increased ratios of HSP110DE9:HSP110, owing to the loss of expression of full-length HSP110. Deletions in HSP110 T17 were mostly biallelic in primary tumor samples with MSI. Patients with stage II–III cancer who received chemotherapy and had large HSP110 T17 deletions (≥5 bp; 18 of 77 patients, 23.4%) had longer times of relapse-free survival than patients with small or no deletions (≤4 bp; 59 of 77 patients, 76.6%) in multivariate analysis (hazard ratio, 0.16; 95% confidence interval, 0.012–0.8; P = .03). We found a significant interaction between chemotherapy and T17 deletion (P = .009). Conclusions: About 25% of patients with stages II–III colorectal tumors with MSI have an excellent response to chemotherapy, due to large, biallelic deletions in the T17 intron repeat of HSP110 in tumor DNA.